15.0k views
5 votes
Got the picture since copying wont work

Got the picture since copying wont work-example-1
User Bdombro
by
6.3k points

2 Answers

4 votes

STEP1:

Equation at the end of step 1

(2²x³• 2) • x³

STEP2:

Multiplying exponents:

2.1 2² multiplied by 2¹ =
2 {}^((2 + 1)) = 2³

Equation at the end of step2:

2³x³ • x³

STEP3:

Multiplying exponential expressions :

3.1 x³ multiplied by x³ =
{x}^((3 + 3)) = x⁶

Final result :

2³x⁶

User Tosh
by
6.3k points
2 votes
The answer is A

8x^6

Because 4x2=8

And simply add the exponents together

3+3=6
User Gopherkhan
by
5.7k points